Barriers and enablers of using a clinical decision support algorithm to consult sick children at primary health facilities: A qualitative study from Uttar Pradesh, India - Mansi Tyagi; Divas Kumar; Kovid Sharma; Fenella Beynon; Gaurav Kumar; Hélène Langet; Gillian A. Levine; Michael A. Ruffo; Mira Emmanuel Fabula; Valérie D'Acremont; Kaspar Wyss; Leah F. Bohle; et al. (Clinical Epidemiology and Global Health, 2025)
Introduction: In Indian public health system, adherence to Integrated Management of Childhood Illness (IMNCI) guidelines is low due to inadequate capacity building, high workload and shortage of healthcare providers (HCPs). Objective was to explore barriers and enablers experienced by HCPs using a digital clinical decision support algorithm (CDSA) for consultation of sick under-five children at primary healthcare facilities in Uttar Pradesh, India. Method: From nine facilities, ten HCPs were trained on IMNCI guidelines and CDSA use. In-depth interviews (IDIs) of HCPs were conducted at three weeks (early phase) and five months (late phase), after intervention initiation. Result: From July-to-December 2022, nine IDIs were conducted in early and eight in late phase. One HCP was paediatrician, five were trained in modern medicine and remaining in Indian traditional medicine systems. Their median clinical experience was 11 years. High patient load, HCP's shortage, multiple responsibilities and lack of supervisory support were identified as facility related barriers to CDSA implementation. Additionally, software glitches, substantial time requirements to complete consultation with CDSA and manual data entry were identified as device-related barriers. Low patient load, perceived value of CDSA by HCPs and ability of CDSA to work offline were identified as enablers. From early to late phase, no strong differences were identified on views about CDSA, with some of the barriers however being stronger. Conclusion: CDSA can enhance access to evidence-based guidelines and improve awareness of assessment and management, as highlighted by HCPs. To fully realize these benefits, system challenges and technological barriers must be addressed.